2001
DOI: 10.1046/j.1365-2249.2001.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of NK cell activation induced by coculture with dendritic cells derived from peripheral blood monocytes

Abstract: SUMMARYDendritic cells (DCs) have been regarded as one of the effective antigen-presenting cells, but the relationship between DCs and lymphocytes, in particular natural killer (NK) cells, remains unclear. In this study, we evaluated how DCs interact with both lymphocytes and NK cells using a coculture system. The number of lymphocytes increased significantly when cocultured with DCs (1´8-fold increase). In particular, the proliferation of NK cells was prominent. Furthermore, the coculture of DCs with lymphocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…Thus, it is likely that other factors could be involved in the NK/DC cross-talk. Several cell surface receptors and soluble factors, such as IL-12, were shown to mediate the NK/DC cross-talk in humans and mice (21,46,(51)(52)(53)(54)(55). These factors, in addition to CD28/CTLA-4, might also be involved in regulating NK cell IFN-g production in response to mDCs in our experimental system.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, it is likely that other factors could be involved in the NK/DC cross-talk. Several cell surface receptors and soluble factors, such as IL-12, were shown to mediate the NK/DC cross-talk in humans and mice (21,46,(51)(52)(53)(54)(55). These factors, in addition to CD28/CTLA-4, might also be involved in regulating NK cell IFN-g production in response to mDCs in our experimental system.…”
Section: Discussionmentioning
confidence: 84%
“…Yu et al (24) demonstrated the capability of CD34 ϩ cell-derived DCs to significantly improve the tumor-directed cytotoxicity and IFN-␥ secretion of NK cells. In addition, it has been shown that the expansion, IFN-␥ production, and tumoricidal potential of NK cells are increased efficiently upon interaction with monocyte-derived DCs (25)(26)(27). Cross-talk is bidirectional because activated NK cells induce immature DC activation in terms of up-regulation of MHC and costimulatory molecules, resulting in an enhancement of the allostimulatory capacity of DCs (28,29).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…The precise events or mediators that direct DC toward immunity or tolerance are not understood. Some have postulated that CD8␣ Ϫ (myeloid) DC are inherently immunogenic while CD8␣ ϩ (lymphoid) DC are tolerogenic (2)(3)(4). However, recent studies have indicated that CD8␣ ϩ and CD8␣ Ϫ DC are not distinct populations but simply represent different maturational stages of the same DC lineage (5).…”
Section: Endritic Cells (Dc)mentioning
confidence: 99%